d DESAIN PENDIDIKAN ISLAM BERWAWASAN ANTI KEKERASAN DAN HAK ASASI MANUSIA: DESAIN PENDIDIKAN ISLAM BERWAWASAN ANTI KEKERASAN DAN HAK ASASI MANUSIA - M Muhyiddin (KAMALIYAH : Jurnal Pendidikan Agama Islam, 2025)
Islamic education has a strategic role in shaping the character and behavior of students to be in harmony with universal values that uphold peace, justice, and humanity. In the modern context, mainstreaming anti-violence values and Human Rights (HAM) has become an urgent need in Islamic education design. This paper aims to formulate the concept of Islamic education design that has anti-violence insight and upholds human rights, with an integrative approach between Islamic teachings and universal human rights principles. This research uses a descriptive qualitative approach with literature studies on primary and secondary sources, both from Islamic and international human rights perspectives. The results of the study show that Islam essentially teaches the values of love, justice, tolerance, and respect for the right to life and human dignity. Ideal Islamic education design should internalize these values in curriculum, learning methods, and educational culture. Thus, Islamic education not only becomes a means of forming knowledge and faith, but also becomes a cultural foundation for creating a generation that rejects violence and upholds human rights. The implementation of this design requires the involvement of all education stakeholders collaboratively and sustainably.